Using behavior and eye-fixations to detect feigned memory impairment - Gomes, Filomena; Ferreira, Inês; Rosa, Bruno; Martins da Silva, Ana; Cavaco, Sara (Frontiers in Psychology, 2024)
Background Detecting invalid cognitive performance is an important clinical challenge in neuropsychological assessment. The aim of this study was to explore behavior and eye-fixations responses during the performance of a computerized version of the Test of Memory Malingering (TOMM-C) under standard vs. feigning conditions. Participants and methods TOMM-C with eye-tracking recording was performed by 60 healthy individuals (31 with standard instruction – SI; and 29 were instructed to feign memory impairment: 21 Naïve Simulators – NS and 8 Coached Simulators – CS) and 14 patients with Multiple Sclerosis (MS) and memory complaints performed. Number of correct responses, response time, number of fixations, and fixation time in old vs. new stimuli were recorded. Nonparametric tests were applied for group comparison. Results NS produced fewer correct responses and had longer response times in comparison to SI on all three trials. SI showed more fixations and longer fixation time on previously presented stimuli (i.e., familiarity preference) specially on Trial 1, whereas NS had more fixations and longer fixation time on new stimuli (i.e., novelty preference) specially in the Retention trial. MS patients produced longer response time and had a different fixation pattern than SI subjects. No behavioral or oculomotor difference was observed between NS and CS. Conclusion Healthy simulators have a distinct behavioral and eye-fixation response pattern, reflecting a novelty preference. Oculomotor measures may be useful to detect exaggeration or fabrication of cognitive dysfunction. Though, its application in clinical populations may be limited.